(untitled) (Al-Academy, 2019)
Garbage is the waste of neglected human beings. The despised thing turns into art. We accept its existence as one of the new aesthetics that have been extended in the joints of modern life. Works of debris and waste find their place in exhibitions, museums and urban spaces of cities. It is one of the major tremors in the transformation of aesthetic taste on the level of art history.In light of these ideas, we are faced with the problem of interpreting the phenomenon and its identity, because the remnants of garbage for each people have historical characteristics and a kind of anthropology that refers to the culture of human use of the materials and their waste and the identity of their belonging. In Iraq, the garbage has its ecological and cultural characteristics in addition to the deposition of a series of wars, Strange remains.This study in its borders is located on the quality, which made the phenomenon of garbage a material for art, and then the answer to the question of changing the artistic and aesthetic taste and the limits of the use of waste in Iraqi art works